Interrogating Large-scale Land Acquisitions and Land Governance in Uganda: Implications for Women’s Land Rights - Ahikire, Josephine; Kanyesigye, Juliet; Nassali, Maria; Nakayi, Rose; Katushabe, Jovah; Pamara, Harriet (My University, 2017)
Land is a key asset for the livelihood of the majority of people and is a key ingredient in the constitution of rights, entitlement as well as identity. Land is a key economic resource for agricultural production and accumulation as well as a key signifier in the constitution of social status and citizenship. Equally so, land disputes tend to constitute the largest percentage of conflict at household and community levels. Because of the potentially volatile nature of land, its governance is a critical issue and land issues have been noted as some of those that demand careful management.